Benchmarking of potential rapid inspection methods for quantitative tracking of thermoset prepreg state evolution with prolonged ambient ageing. (1st April 2023) - Smith, Adam W.; Hubert, Pascal
Abstract: Extensive ambient ageing of prepregs has been shown to bring about reduction in tack and gel time, while increasing ply in-plane and bending stiffness as well as resin processing viscosity. These changes increase the likelihood of defects forming during manufacturing of parts such as ply bridging, wrinkling and incomplete resin impregnation. Quality standards which strictly control prepreg storage conditions have been used to limit the negative effects of ageing and ensure consistent part quality. However, these same inflexible standards are responsible for the landfilling of many unfinished prepreg rolls given insufficient recycling options. In this article, three well established experimental techniques (DSC, FT-IR, and GPC) are used to follow the ambient ageing of a commercially available aerospace prepreg for periods of up to 375 days. Ageing metrics such as glass transition temperature are identified for each method and used to quantitatively track and compare changes in prepreg state. Finally, the potential of each method as a rapid inspection tool is discussed based on material and time requirements.